ANALYSIS OF READING INTEREST USING PICTURED STORYBOOK MEDIA IN GRADE III STUDENTS OF KALIBUNTU STATE ELEMENTARY SCHOOL - Siti Julaeha; Ari Gunardi; Fajar Yumanhadi Arifin (Cakrawala Pedagogik, 2025)
Reading interest is one of the important factors in the success of learning for elementary school students. However, in reality, students’ reading interest is still relatively low. This study aims to analyze the reading interest of third grade students at SD Negeri Kalibuntu by using picture storybooks as a learning medium. This research employed a descriptive qualitative approach with the research subjects being third grade students at SD Negeri Kalibuntu. Data were collected through questionnaires, observations, and interviews covering four indicators of reading interest, namely reading enjoyment, awareness of the benefits of reading, reading frequency, and the quantity of reading sources. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The results of the study show that the use of picture storybooks can foster students’ reading interest in all observed indicators. Students became more enthusiastic about reading, more aware of the benefits of reading, increased their reading frequency, and expanded the variety of reading sources. Thus, picture storybooks are proven to be relevant and effective in enhancing elementary school students’ reading interest.